Article 13 on social media and news media: disintermediation and reintermediation on the modern media landscape - Moreno, J.; Sepúlveda, R. (Communication and Society, 2021)
The former Article 13 (now Article 17) of the European directive on copyright and the internet (Directive EC2019/790) has been under negotiations since 2016 and was finally approved in 2019. In Portugal, however, the issue was mostly absent from public scrutiny and debate until November 2018. In that month, the issue arose to a prominent level, both in news media and in social media, following a wave of alerts issued by various young youtubers, incentivized by YouTube management. In this paper, we engage in the discussion concerning disintermediation, studying the way in which such alerts spread both in news media and social media, and understanding the role played by the users of social media platforms in modelling the social relevance and the social discourse of the issue of copyright and the internet. To do so, we used digital methods, collecting and analysing data from Twitter, YouTube and from online news media, mapping Article 13 discussions and identifying key actors in each field, as well as the connections between them. The results show that the ease of access provided by platforms such as Twitter or YouTube converts some users to prominent influencers and that, in some cases, those influencers are able to shift and model the public discourse about relevant collective issues.